New ecdysone receptor agonists: a computational approach for rational discovery of insecticides for crop protection. Issue 11 (25th August 2021) - Singh, Rahul; Bhardwaj, Vijay Kumar; Das, Pralay; Purohit, Rituraj
Abstract : Plant derived ( C. deodara ) in-house synthesized molecules with benzosuberene scaffolds as potential EcR agonists to target Hemiptera and Coleoptera. Abstract : An ecdysone receptor (EcR) is a nuclear receptor protein, a prime target for pesticide development processes due to its involvement in the growth and development of insects. The activation of EcRs leads to hasty and premature development of insects, thereby preventing them from destroying the crops. The high cost, environmental toxicity, and resistance towards the currently available insecticides have resulted in a growing demand for the development of economical and environment-friendly pesticides with unique insecticidal activity. Several reports on resistance towards conventional pesticides like ponasterone A and RH-5849 were reported in recent years. In this study, the plant derived ( C. deodara ), in-house synthesized molecules with benzosuberene scaffolds were screened for their ability to interact with the EcRs of both Hemiptera and Coleoptera. The preliminary analysis by molecular docking showed that some of our molecules exhibited excellent binding with the target protein. Moreover, molecular dynamics simulations, binding free energy estimations, and umbrella sampling simulations were conducted to validate the docking results. Our analysis revealed Com-7 and Com-3 as potential EcR agonists to target Hemiptera and Coleoptera, respectively. Also, Com-8 and Com-12 could be used as lead compounds against the EcR of Coleoptera.